Engines and Fuels for Future Transport - Kalghatgi, Gautam; Agarwal, Avinash Kumar; Leach, Felix; Senecal, Kelly; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book focuses on clean transport and mobility essential to the modern world. It discusses internal combustion engines (ICEs) and alternatives like battery electric vehicles (BEVs) which are growing fast. Alternatives to ICEs start from a very low base and face formidable environmental, material availability, and economic challenges to unlimited and rapid growth. Hence ICEs will continue to be the main power source for transport for decades to come and have to be continuously improved to improve transport sustainability. The book highlights the need to assess proposed changes in the existing transport system on a life cycle basis. The volume includes chapters discussing the challenges faced by ICEs as well as chapters on novel fuels and fuel/ engine interactions which help in this quest to improve the efficiency of ICE and reduce exhaust pollutants. This book will be of interest to those in academia and industry alike.
Introduction to Engines and Fuels for Future Transport -- Sustainable Transportation -- A review of emissions control technologies for on-road vehicles -- Opposed-Piston Engine Renaissance: Low CO2 and Criteria Emissions -- An Overview of Hybrid Electric Vehicle Technology -- Life-Cycle Analysis for the Automotive Sector -- Pre-Chamber Combustors: An Enabling Technology for High Efficiency, Low CO2 Engine Operation -- Pathway to Ultra-Lean IC engine combustion: Narrow Throat Pre-chamber -- Active Pre-Chamber with Bio-Hybrid Fuels -- The Use of Ammonia as a Fuel for Combustion Engines.
Keywords: Engines; Sustainability; Pollution; Cogeneration of electric power and heat; Fossil fuels; Transportation engineering; Traffic engineering; Engine Technology; Sustainability; Pollution; Fossil Fuel; Transportation Technology and Traffic Engineering; Fuel; Internal combustion engines; Sustainable transportation